Strengthening one health: Lessons learned of rabies response in Indonesia - Thursina Tanrypada; Hasanbasri Mubasysyir; Mahendradhata Yodi (BIO Web of Conferences)
In recent years, zoonoses have continued to pose a threat to global health, including in Indonesia. Avian influenza infections, rabies cases that remain endemic in many regions, and the COVID-19 pandemic are concrete examples of the dangers of zoonoses. These health issues can be prevented and addressed through the cross-sectoral collaboration for the One Health concept. The One Health concept emphasizes the interconnection between the health sector, animal health, and the environmental sector. One Health concept also promotes essential cross-sectoral collaboration in preventing and controlling zoonoses. As a concept that emphasizes various sectors to address the complex issue of zoonoses, it significantly aids in the rapid and accurate response to case reports and outbreak investigations. However, many health and veterinary health workers are unaware of or do not understand this concept. The lack of knowledge among these workers about the One Health concept can be problematic in managing zoonotic cases in the future, especially given the changing epidemiology of many zoonotic diseases. Despite cross-sectoral collaboration, the absence of the One Health approach results in fragmented and uncoordinated responses to zoonotic case reports, making handling less effective and proactive. Therefore, it is necessary to systematically introduce this concept to health and veterinary health workers through integrated and sustainable educational programs. Education about One Health enhances the skills and capacity of health and veterinary health workers and strengthens the national health system. It also can help to initiate collaboration between the two sectors in a sustainable manner to manage and control zoonotic disease and bridging the gap between them. This collaboration will enable better coordinated and integrated responses to zoonotic threats, ultimately improving the overall efficacy of disease prevention and control programs. Comprehensive introduction and training on One Health must become a priority to ensure that zoonoses do not continue developing and threaten public health in Indonesia.